In Vitro Release Kinetics of Antituberculosis Drugs from Nanoparticles Assessed Using a Modified Dissolution Apparatus. (10th July 2013) - Gao, Yuan; Zuo, Jieyu; Bou-Chacra, Nadia; Pinto, Terezinha de Jesus Andreoli; Clas, Sophie-Dorothee; Walker, Roderick B.; Löbenberg, Raimar
Abstract : The aim of this study was to assess the in vitro release kinetics of antituberculosis drug-loaded nanoparticles (NPs) using a "modified" cylindrical apparatus fitted with a regenerated cellulose membrane attached to a standard dissolution apparatus (modifiedcylinder method). The model drugs that were used were rifampicin (RIF) and moxifloxacin hydrochloride (MX). Gelatin and polybutyl cyanoacrylate (PBCA) NPs were evaluated as the nanocarriers, respectively. The dissolution and release kinetics of the drugs from loaded NPs were studied in different media using the modified cylinder method and dialysis bag technique was used as the control technique. The results showed that use of the modified cylinder method resulted in different release profiles associated with unique release mechanisms for the nanocarrier systems investigated. The modified cylinder method also permitted discrimination between forced and normal in vitro release of the model drugs from gelatin NPs in the presence or absence of enzymatic degradation. The use of dialysis bag technique resulted in an inability to differentiate between the mechanisms of drug release from the NPs in these cases. This approach offers an effective tool to investigate in vitro release of RIF and MX from NPs, which further indicate that this technique can be used for performance testing of nanosized carrier systems.